2020
DOI: 10.3389/fimmu.2020.00458
|View full text |Cite
|
Sign up to set email alerts
|

The Role of B7 Family Molecules in Maternal–Fetal Immunity

Abstract: Pregnancy is a complex but well-arranged process, and a healthy fetus requires immune privilege and surveillance in the presence of paternally derived antigens. Maternal and fetal cells interact at the maternal-fetal interface. The upregulation and downregulation of maternal immunity executed by the leukocyte population predominantly depend on the activity of decidual natural killer cells and trophoblasts and are further modulated by a series of duplex signals. The B7 family, which consists of B7-1, B7-2, B7-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 100 publications
1
34
0
Order By: Relevance
“…It has been suggested that elucidation of the role of SMG6 may aid in explaining the maintenance of SARS‐CoV‐2 persistence. In addition to these 12 genes, some other genes whose differential methylation sites were identified in the gene body may also play crucial roles, such as BTNL2 , which is involved in multiple inflammatory and autoimmune diseases (Zhao et al., 2020 ). Whether these DMGs, can be used as new biomarkers of SARS‐CoV‐2 infection need further study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that elucidation of the role of SMG6 may aid in explaining the maintenance of SARS‐CoV‐2 persistence. In addition to these 12 genes, some other genes whose differential methylation sites were identified in the gene body may also play crucial roles, such as BTNL2 , which is involved in multiple inflammatory and autoimmune diseases (Zhao et al., 2020 ). Whether these DMGs, can be used as new biomarkers of SARS‐CoV‐2 infection need further study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of co-signaling molecules at the feto-maternal interface, such as checkpoint molecules of the B7 family, has been recently highlighted. 85 The outer layer of the placenta, formed by completely differentiated syncytiotrophoblastic cells, expresses PD-L1 abundantly. As mentioned above, this molecule is unfortunately only rarely expressed in childhood cancer.…”
Section: Similarities Between Placenta and Childhood Cancermentioning
confidence: 99%
“…Studies reported that MTHFR was an important candidate gene for sheep milk yield traits [59,60]. NPPB, BTNL2, TAP2, and WASF3 were involved in PI3K/AKT, Ca 2+ , K + , ATP, and immunity [45,[61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%